Population and distribution of Sunda porcupine (Hystrix javanica F. Cuvier, 1823) in designated area of Cisokan Hydropower, West Java, Indonesia - IRINA A MUSTIKASARI; SUSANTI WITHANINGSIH; ERRI N MEGANTARA; TEGUH HUSODO; PARIKESIT PARIKESIT (Biodiversitas Journal of Biological Diversity, 2019)
Abstract. Mustikasari IA, Withaningsih S, Megantara EN, Husodo T, Parikesit. 2019. Population and distribution of Sunda porcupine (Hystrix javanica F. Cuvier, 1823) at designated area of Cisokan Hydropower, West Java, Indonesia. Biodiversitas 20:  762-769. One of the endemic species of Indonesia is the Sunda porcupine (Hystrix javanica). Sunda porcupine is a big rodent which has unique defense mechanism behavior using its quills. This research was conducted in the designated area of Cisokan Hydropower (PLTA Cisokan), in West Java, Indonesia. The method in this study is qualitative to determine the total population and distribution. Data collection techniques were carried out by sign surveys (burrow, footprints, quills, food sites, and feces), camera traps, and semi-structured interviews. The result shows the number of porcupine populations in the designated area of Cisokan Hydropower is 6-29 individuals. Porcupine population is distributed in five regions, namely the first region consisting of Pasir Gagak, Cigintung, Batu Sahulu and Batu Nunggul; the second region is Batu Tumpeng and Batu Wulung; the third region is Curug Japarana; the fourth region consists of Sarongge and Cadas Gantung; and the fifth region is Pongpok. Based on the type of land cover, the porcupine population is commonly found in the types of shrub/huma /ladang, talun, and natural forests.